Measuring The Contribution Of Financial Literacy In Building The Competitive Advantage Of MSMEs In Indonesia : Systematic Literature Review (SLR) - Amelia Sugangga; Puji Handayati; Arief Noviarakhman Zagladi (Pusat Riset dan Inovasi Nasional, 2023)
A country's economic growth cannot be separated from the role of Micro, Small and Medium Enterprises (MSMEs) as the backbone of a strong economy. MSMEs experience various problems, including limited access to resources, inadequate infrastructure, and the inability to compete on a larger scale. These factors become obstacles for MSMEs to optimize their potential and compete in an increasingly complex market . It is important for MSME players to improve their product advantages or marketing strategies, because MSMEs are one of the important business sectors in Indonesia. There are not many studies that systematically measure the contribution of financial literacy in building the competitive advantage of MSMEs, especially in the Indonesian context. This research tries to open a new space by using the Systematic Literature Review (SLR) method to detail the understanding of the concept of financial literacy and its implications for the competitive advantage of MSMEs in Indonesia. The importance of this research lies in the urgency to provide a more comprehensive view of how financial literacy can make a concrete contribution in establishing and maintaining the competitive advantage of MSMEs. Results of this research state that Financial literacy has a significant role in helping MSMEs face financial challenges and compete in a dynamic market. It is hoped that the results of this research can provide practical and policy implications for stakeholders, government and business people in increasing the financial literacy of MSMEs, so as to create an environment that supports the growth and competitiveness of MSMEs in Indonesia.